Influence of the Phenological Stage and Harvest Date on the Bioactive Compounds Content of Green Pepper Fruit - Alicia Dobón-Suárez; María J. Giménez; Salvador Castillo; María E. García-Pastor; Pedro J. Zapata (Molecules, 2021)
Green pepper fruit is often consumed before it is completely ripe. However, the influence of the phenological stage in which the green pepper is consumed as a potential influencing factor in its bioactive compounds content and antioxidant capacity remains unknown. In addition, no literature is available concerning the bioactive compounds changes in ‘Lamuyo’ green peppers along its developmental and growth cycle. For this, two different approaches have been carried out, one using twelve different phenological stages (S1 to S12), and in the other, seven different harvest dates (from 27 February to 20 April). Moreover, bioactive compounds changes during 21 days of postharvest storage at 8 °C were investigated. In this study, bioactive compounds (ascorbic acid, dehydroascorbic acid, and total phenolic content) and the total hydrophilic and lipophilic (TAA-H and TAA-L) antioxidant activity were analysed. In addition, total soluble solids, total acidity, individual sugars, and organic acids were determined. Vitamin C levels increased along the phenological stages and harvest dates due to significant increases in ascorbic and dehydroascorbic acid levels. Our results show that the total phenol content decreases as vegetables develop and subsequently increases both as ripening begins and by the last harvest date. Furthermore, TAA-H was also greater by the phenological stage S12 and the 20 April harvest date. In conclusion, the phenological stage and harvest date are key factors that significantly influence the bioactive compounds of green peppers, and those that appear by S12 and 20 April could be more beneficial to health.